A personal leadership statement (2025)
This paper explores the concept and nature of leadership with a transformational approach in the educational context of foreign language teaching, specifically English. Through the analysis of foundations proposed by leading authors such as Daft and Northouse, the importance of team learning, collaboration and empowerment are discussed. Throughout the analysis, the author's personal perspectives on these issues are also included. At the end of the essay, a plan for implementing leadership and empowerment practices in learning is proposed, integrating theoretical foundations and personal experiences in order to highlight the value of leadership in education.